Identification of herring populations - Lísa Anne Libungan 1977- (2015)
Information on population structure is important for the successful management of harvested species and for the understanding of the distributional range, migration behaviours and for protection of biodiversity. Atlantic herring (Clupea harengus Linnaeus 1758) is one of the most abundant fish species in the world and due to its commercial value, an understanding of its biology, including its population dynamics, is needed for the sustainable management of the resource. The biogeography of herring is highly complex and populations are often defined on the basis of where and when they spawn. In this study, I have developed two tools to discriminate between herring populations. Microsatellite markers for genetic analysis and a statistical package (shapeR) to study otolith shape. Extensive sampling of two herring species, Atlantic and Pacific herring (Clupea pallasii Valenciennes 1847), was conducted throughout the North Atlantic, along the coast of Norway, Russia, and the Pacific. Analysis of variation in the microsatellite markers did not detect any differentiation among the herring stocks in the North Atlantic, however, otolith shape variation was detected. These differences could be traced to three morphological structures on the otolith outlines which showed a correlation with the stocks spawning time. A classifier based on the shape differences was able to discriminate with 94% accuracy between the Icelandic summer-spawners and the Norwegian spring-spawners, which are known to mix at feeding grounds east of Iceland. In separate studies on local populations in Norway, variation in otolith shape was detected, and among local populations along the coast, a latitudinal gradient emerged where neighbouring populations were more similar to each other than to those sampled at larger distances. These morphological differences are likely to reflect environmental differences but also indicate low dispersal among the local herring populations. At the species level, a comparison in otolith shape was conducted between ...